DETERMINAN INTEGRITAS LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR DI INDONESIA - Paramita Hana Saksakotama; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
Financial Statement is the one of very important components to make decisions for stakeholders, bondholders and others. Integrity is one of use fullthings to increase the accuration of financial statement and the quality of decision making. It helps companies to increase financial information with faithfulness representation and reduce agency costs of minimize conflict of interest. The conservatism is used to explain integrity of financial statements as signal positive for companies to attract investors, because agreeing conservatism for preparation of financial statements will increase quality of income. This research examines the application of integrity of financial statements in companies and the determinants of integrity of financial statements. The sample of this research is Indonesian manufacturing companies which is listed in 2008 to 2012 at Indonesian Stock Exchange. They have all of the components which are used for this research, such as inventory method. The results indicate that some determinants of integrity of financial statements such as managerial ownership, independent commissioners, KAP size, firm size and auditor tenure have significant effect to integrity of financial statement. However, the other factors such as institutional ownership and independence audit committee do not explain the application of high integrity in the financial statements of the companies.